2011
DOI: 10.1159/000330416
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and Cardiovascular Risk in Cushing’s Syndrome

Abstract: Cushing’s syndrome (CS) is associated with increased cardiovascular morbidity and mortality. Recent evidence also suggests that increased cardiovascular risk may persist even after long-term remission of CS. Increased central obesity, a typical feature of CS, is associated with altered production of adipokines, which contributes to the pathogenesis of several metabolic and cardiovascular complications observed in this condition. In vitro and in vivo studies have shown a relationship between cortisol and adipok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 378 publications
(267 reference statements)
3
45
0
2
Order By: Relevance
“…In human medicine, hyperleptinemia in patients with Cushing's syndrome is related to a higher prevalence of cardiovascular diseases11 and it has been suggested that hyperleptinemia has proinflammatory, prothrombotic, and pro‐oxidant effects 33. The present findings suggest that the development and progression of complications related to HAC are probably associated with hyperleptinemia, although future longitudinal studies in dogs with HAC are required to support or refute this.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In human medicine, hyperleptinemia in patients with Cushing's syndrome is related to a higher prevalence of cardiovascular diseases11 and it has been suggested that hyperleptinemia has proinflammatory, prothrombotic, and pro‐oxidant effects 33. The present findings suggest that the development and progression of complications related to HAC are probably associated with hyperleptinemia, although future longitudinal studies in dogs with HAC are required to support or refute this.…”
Section: Discussionmentioning
confidence: 53%
“…Inflammatory cytokines were detected in several overweight dogs with PDH, although we did not examine the source of these cytokines so it is not clear if they were produced by adipose tissue (as is possible34), or whether there was infectious disease (to which dogs with HAC are prone). In human medicine, it has also been suggested that chronic hypercortisolemia in patients with Cushing's syndrome affects serum TNF‐α and IL‐6 levels, thereby contributing to the persistence of a low‐grade inflammatory state 11. However, further studies will be necessary to clarify the relationships between hyperleptinemia or inflammatory cytokines and the well‐known complications in dogs with HAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that obesity is crucial when considering adiponectin levels in CS patients (113). Conflicting data have been reported about adiponectin levels before and after resolution of CS (104,114,115).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…It would be tempting to enter data on the glucocorticoid-induced leptin resistance [42,43] and on the elevation of leptin level in patients with Cushing's syndrome [44,45], confirmed by the experiments in vitro [46], but no association was found between leptin levels and BFD patterns [47].…”
Section: Discussionmentioning
confidence: 99%